High-Frequency Oscillatory Ventilation in Pediatric Acute Lung Injury: A Multicenter International Experience*. Issue 12 (December 2015) - Rettig, Jordan S.; Smallwood, Craig D.; Walsh, Brian K.; Rimensberger, Peter C.; Bachman, Thomas E.; Bollen, Casper W.; Duval, Els L.; Gebistorf, Fabienne; Markhorst, Dick G.; Tinnevelt, Marcel; Todd, Mark; Zurakowski, David; et al.
Abstract : Objective: We aim to describe current clinical practice, the past decade of experience and factors related to improved outcomes for pediatric patients receiving high-frequency oscillatory ventilation. We have also modeled predictive factors that could help stratify mortality risk and guide future high-frequency oscillatory ventilation practice. Design: Multicenter retrospective, observational questionnaire study. Setting: Seven PICUs. Patients: Demographic, disease factor, and ventilatory and outcome data were collected, and 328 patients from 2009 to 2010 were included in this analysis. Interventions: None. Measurement and Main Results: Patients were classified into six cohorts based on underlying diagnosis. We used univariate analysis to identify factors associated with mortality risk and multivariate logistic regression to identify independent predictors of mortality risk. An oxygenation index greater than 35 and immunocompromise exhibited the greatest predictive power ( p < 0.0001) for increased mortality risk, and respiratory syncytial virus was associated with lowest mortality risk ( p = 0.003). Differences in mortality risk as a function of oxygenation index were highly dependent on primary underlying condition. A trend toward an increase in oscillator amplitude and frequency was observed when compared with historical data. Conclusions: Given the number of centers and subjects included in the database, these findings provide a robust description of current practice regarding the use of high-frequency oscillatory ventilation for pediatric hypoxic respiratory failure. Patients with severe hypoxic respiratory failure and immunocompromise had the highest mortality risk, and those with respiratory syncytial virus had the lowest. A means of identifying the risk of 30-day mortality for subjects can be obtained by identifying the underlying disease and oxygenation index on conventional ventilation preceding the initiation of high-frequency oscillatory ventilation. Abstract : Supplemental Digital Content is available in the text.